Mat material, exhaust gas purification device, and method for manufacturing exhaust gas purification device
By designing the inorganic fiber cushion material and surface treatment with specific structures, the problem of deformation of the cushion material when pressed is solved, and the stability and purification effect of the exhaust gas treatment body are improved.
Patent Information
- Application Number
- CN202380044439.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-05-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing cushion material is prone to deformation when pressed, causing part to be exposed from the shell, affecting the fixing and purification effect of the exhaust gas treatment body.
An inorganic fiber cushion material is designed, characterized by having a specific convex and concave structure during winding, and the ratio of the non-concave length in the width direction to the non-concave length in the length of the non-concave portion is 1.0 or more, which enhances the Resistance to shear stress is performed and needle-punched on the surface or back surface or adhesive is added to improve friction resistance and adhesion.
It effectively suppresses deformation and deviation of the cushion material when pressed, ensures the stability and purification effect of the exhaust gas treatment body, and avoids the problem of the cushion material being exposed from the shell.
Smart Images

Figure CN119317770A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a mat material, an exhaust gas purification device and a method for manufacturing the exhaust gas purification device. Background Art
[0002] Exhaust gas discharged from internal combustion engines such as diesel engines contains particulate matter (hereinafter also referred to as PM), and in recent years, the PM has become a problem of harming the environment and human body. In addition, since the exhaust gas also contains harmful gas components such as CO, HC, and NOx, there is also concern that these harmful gas components will affect the environment and human body.
[0003] Here, as an exhaust gas purification device for capturing PM in exhaust gas and purifying harmful gas components, various schemes of exhaust gas purification devices are proposed, which are composed of an exhaust gas treatment body (which is composed of porous ceramics such as silicon carbide and cordierite), a shell that accommodates the exhaust gas treatment body, and a mat material formed of an inorganic fiber aggregate arranged between the exhaust gas treatment body and the shell. The main purpose of arranging such a mat material is to prevent the exhaust gas treatment body from contacting with the shell covering its outer periphery and being damaged due to vibration or impact caused by the driving of the car, etc., and to prevent exhaust gas from leaking from between the exhaust gas treatment body and the shell, etc.
[0004] The above-mentioned mat material is composed of inorganic fibers. The basic shape of the above-mentioned mat material when viewed from above is a rectangle consisting of long sides extending in the length direction and short sides approximately perpendicular thereto. A recess is formed on one short side of the above-mentioned rectangle, and a convex portion consisting of a shape identical to the shape cut off by the above-mentioned recess is formed on the other short side. The above-mentioned mat material is wound around the exhaust gas treatment body so that the above-mentioned convex portion is engaged with the above-mentioned recess, thereby preventing exhaust gas from leaking from the mat material.
[0005] The exhaust gas treatment body with the mat material wound around it is pressed into the casing and assembled in the exhaust gas purification device.
[0006] For example, Patent Document 1 discloses the following: by using a sheet (pad material) having an average value h of the unevenness difference in the range of 0.4mm≤h≤9mm on the first surface, the contact area between the sheet and other components is reduced, thereby making it possible to easily install the sheet in a specified position without using a surface lubricant.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2011-241837 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Patent document 1 does not mention the small size of the recessed and convex portions. After the mat is manufactured and pressed in, a portion of the mat arranged on the upstream side of the fitting portion is deformed. When the exhaust gas treatment body is fixed in a specified position, a portion of the mat is sometimes exposed from the outer shell.
[0012] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a mat member which is less likely to be exposed from a housing when pressed.
[0013] Means for solving problems
[0014] That is, the mat material of the present invention is a mat material that is roughly rectangular in plan view and contains inorganic fibers, and is characterized in that the mat material has: a first main surface and a second main surface facing each other in the thickness direction; a first end surface and a second end surface facing each other in the length direction that becomes the winding direction; and a first side surface and a second side surface facing each other in the width direction that is orthogonal to the thickness direction and the length direction, wherein the first end surface is provided with: a convex portion that protrudes toward the second end surface when winding, and a non-protruding portion that is arranged on both sides of the convex portion in the width direction and does not protrude toward the second end surface, and the second end surface is provided with: a concave portion that corresponds to the shape of the convex portion of the first end surface when winding, and a non-depressed portion that is arranged on both sides of the concave portion in the width direction and corresponds to the shape of the non-protruding portion of the first end surface, and the ratio [D / C] of the length [D] of the non-depressed portion in the width direction to the length [C] of the non-depressed portion in the length direction is greater than 1.0.
[0015] When the mat having corresponding convex and concave portions described in Patent Document 1 is wound around an exhaust gas treating body, a portion of the first end surface and a portion of the second end surface are alternately arranged at a fitting portion where end surfaces of the mat fit together.
[0016] A portion of the first end surface refers to a convex portion provided on the first end surface, and a portion of the second end surface refers to a non-concave portion provided on the second end surface. There are two non-concave portions of the second end surface, one disposed on the first side surface, and the other disposed on the second side surface. When winding, the shapes of the convex portion of the first end surface and the concave portion of the second end surface, and the shapes of the non-protruding portion of the first end surface and the non-concave portion of the second end surface correspond to each other.
[0017] When pressed into the housing, shear stress is generated between the exhaust gas treatment body and the housing, so the mat material is easily deformed by stretching toward the upstream side of the pressing direction. This deformation is particularly likely to occur in the non-depressed portion on the upstream side where there is no structure that hinders deformation, that is, the non-depressed portion arranged on the most upstream side.
[0018] Regarding the non-depressed portion, it is believed that the closer the portion is to the mat material body (the portion other than the convex portion and the non-depressed portion), the less likely it is to be deformed by shear force, and the farther away from the mat material body, the easier it is to be deformed by shear force. In other words, it can be said that the shorter the length of the non-depressed portion, the less likely it is to be deformed.
[0019] On the other hand, it can be said that the longer the width of the non-recessed portion (the distance equivalent to the length from the first side or the second side to the recessed portion), the longer the area in which the non-recessed portion is fixed to the mat body, and therefore the less likely it is to deform due to shearing.
[0020] That is, it is considered that the ease of deformation of the non-recessed portion can be improved by adjusting the length and width of the non-recessed portion.
[0021] Furthermore, even when there are a plurality of convex portions on the first end surface and a plurality of concave portions on the second end surface, the above-mentioned effects are achieved.
[0022] In the mat of the present invention, a ratio [D / C] of a length [D] of the non-depressed portion in the width direction to a length [C] of the non-depressed portion in the longitudinal direction is 1.0 or more.
[0023] The above configuration can be said to be a configuration in which the length [C] of the non-recessed portion in the longitudinal direction is relatively short and the length [D] of the non-recessed portion in the width direction is relatively long compared to the configuration of Patent Document 1.
[0024] Therefore, if the shape of the mat material satisfies the above conditions, the non-recessed portion is less likely to be deformed by the shear force during press-fitting and is less likely to be exposed from the outer shell.
[0025] The mat material of the present invention is preferably a needle punched mat.
[0026] The mat material of the present invention is preferably a mat material having a plurality of interlacing points formed by needle punching on at least one of the surface or the back surface, wherein at least one of the first area and the second area is arranged in an area of 25mm×25mm, the first area is a 4mm×4mm area where the above-mentioned interlacing points do not exist, and the second area is a 3mm×8mm area where the above-mentioned interlacing points do not exist.
[0027] If the first region and / or the second region is arranged in the region of 25 mm×25 mm, the surface pressure of the mat can be increased.
[0028] In the mat of the present invention, the inorganic fibers preferably have an average fiber length of 1 mm to 150 mm.
[0029] The mat of the present invention is preferably a paper-made mat.
[0030] In the mat of the present invention, the inorganic fibers preferably have an average fiber length of 200 μm to 20,000 μm.
[0031] In the mat material of the present invention, it is preferred that an inorganic binder is attached to the surface of the inorganic fibers.
[0032] When an inorganic binder is attached to the surface of the inorganic fibers, the frictional resistance between the inorganic fibers increases due to the inorganic binder attached to the surface of the inorganic fibers, so that the holding force can be improved.
[0033] In the mat material of the present invention, it is preferred that an organic binder is added to the surface of the inorganic fibers.
[0034] When an organic binder is added to the surface of the inorganic fibers, the adhesion between the inorganic fibers can be improved, and the inorganic fibers can be prevented from scattering during the handling of the mat.
[0035] In the mat material of the present invention, it is preferred that an inorganic binder and an organic binder are attached to the surface of the inorganic fibers.
[0036] When an inorganic binder is attached to the surface of the inorganic fibers, the frictional resistance between the inorganic fibers increases due to the inorganic binder attached to the surface of the inorganic fibers, so that the holding force can be improved.
[0037] Furthermore, when an organic binder is added to the surface of the inorganic fibers, the adhesion between the inorganic fibers can be improved, and the inorganic fibers can be prevented from scattering during the handling of the mat.
[0038] The mat material of the present invention preferably further contains a polymer dispersant.
[0039] When the mat material further contains a polymer-based dispersant, the organic binder and the inorganic binder can be easily attached to the surface of the inorganic fiber in a dispersed state.
[0040] In the mat material of the present invention, it is preferred that the inorganic binder and the organic binder are attached to the surface of the inorganic fibers in a dispersed state.
[0041] If the inorganic binder and the organic binder are respectively attached to the surface of the inorganic fiber in a dispersed state, the inorganic binder is dispersed in the film formed by the organic binder. The film in this state has excellent mechanical strength, so it can prevent the inorganic fibers from sliding against each other and improve the holding force.
[0042] In the mat material of the present invention, it is preferred that an aggregate composed of the inorganic binder and the organic binder is attached to the surface of the inorganic fiber.
[0043] When the aggregate composed of the inorganic binder and the organic binder is attached to the surface of the inorganic fibers, the friction between the inorganic fibers can be increased, thereby improving the holding force.
[0044] In the mat material of the present invention, it is preferred that the covering layer composed of a mixture of the inorganic binder and the organic binder covers at least a part of the surface of the inorganic fibers.
[0045] The coating layer composed of a mixture of an inorganic binder and an organic binder has higher mechanical strength than a coating layer composed of only an organic binder, so that the coating layer is less likely to peel off, and the friction resistance between the inorganic fibers can be increased.
[0046] In the mat material of the present invention, the covering layer is preferably formed by a continuous scaly mixture of the inorganic binder and the organic binder.
[0047] When the coating layer is formed of the scaly mixture, the surface roughness of the coating layer due to the scaly mixture increases, and thus the frictional resistance between the inorganic fibers can be further increased.
[0048] In the mat material of the present invention, the coating layer preferably has a multi-step shape.
[0049] When the coating layer has a multi-step shape, the frictional resistance between the inorganic fibers can be further increased.
[0050] In the mat material of the present invention, it is preferred that a granular mixture of the inorganic binder and the organic binder is adhered to the surface of the covering layer.
[0051] When a particulate mixture of an inorganic binder and an organic binder is attached to the surface of the covering layer, the frictional resistance between the inorganic fibers can be further increased compared to the case of the covering layer alone.
[0052] In the mat of the present invention, a ratio [A / C] of the length [A] of the mat in the longitudinal direction to the length [C] of the non-depressed portion in the longitudinal direction is preferably 10 or more.
[0053] When the ratio [A / C] of the length [A] of the mat in the longitudinal direction to the length [C] of the non-recessed portion in the longitudinal direction is within the above range, the shape of the non-recessed portion becomes less likely to deform during press-fitting.
[0054] The exhaust gas purifying device of the present invention comprises a casing, an exhaust gas treating body, and a mat material arranged between the casing and the exhaust gas treating body, wherein the mat material is the mat material of the present invention.
[0055] Since the exhaust gas purifying device of the present invention includes the mat material of the present invention, the mat material is not exposed during press-fitting, and the exhaust gas treating body has excellent stability.
[0056] The manufacturing method of the exhaust gas purification device of the present invention is characterized by comprising a pressing step: after the mat of the present invention is wound around the exhaust gas treatment body, it is pressed into the housing by a hard filling method, a pre-calibration method or a post-calibration method.
[0057] The hard filling method, the pre-calibration method, and the post-calibration method all require a step of pressing the exhaust gas treatment body with the mat wound around it into the housing. Therefore, the mat of the present invention can suppress the displacement and deformation of the mat during pressing, and is therefore particularly suitable for the above methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a perspective view schematically showing an example of the mat material of the present invention.
[0059] Figure 2 It is a schematic diagram showing Figure 1 A perspective view showing an example of a process of winding a mat material around an exhaust gas treating body.
[0060] Figure 3 is schematically shown in Figure 2 A perspective view of an example of a wound body prepared in the steps shown.
[0061] Figure 4 It shows that Figure 3 Schematic diagram of an example of a step of pressing a wound body into a casing.
[0062] Figure 5 This is a schematic diagram showing an example of the arrangement of interlaced points in the mat of the present invention.
[0063] Figure 6 This is a schematic diagram showing an example of a mat material in which interlacing points are evenly arranged.
[0064] Figure 7 This is an example of an electron microscope image of the mat material of the present invention which is magnified.
[0065] Figure 8 This is another example of an electron microscope image of the mat material of the present invention which is magnified.
[0066] Fig. 9 This is another example of an electron microscope image of the mat material of the present invention which is magnified.
[0067] Fig.10 This is another example of an electron microscope image of the mat material of the present invention which is magnified.
[0068] Fig.11 1 is a conceptual diagram schematically showing a shear failure load test device.
[0069] Fig.12 This is a cross-sectional view schematically showing an example of the exhaust gas purification device of the present invention. DETAILED DESCRIPTION
[0070] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments, and can be applied with appropriate changes within the scope of the gist of the present invention.
[0071] [Material]
[0072] The mat material of the present invention is a mat material that is roughly rectangular in plan view and contains inorganic fibers, and is characterized in that the mat material has: a first main surface and a second main surface facing each other in the thickness direction; a first end surface and a second end surface facing each other in the length direction that becomes the winding direction; and a first side surface and a second side surface facing each other in the width direction that is orthogonal to the thickness direction and the length direction, wherein the first end surface is provided with: a convex portion that protrudes toward the second end surface when winding; and a non-protruding portion that is arranged on both sides of the width direction of the convex portion and does not protrude toward the second end surface, and the second end surface is provided with: a concave portion that corresponds to the shape of the convex portion of the first end surface when winding; and a non-depressed portion that is arranged on both sides of the width direction of the concave portion and corresponds to the shape of the non-protruding portion of the first end surface, and the ratio [D / C] of the length [D] of the non-depressed portion in the width direction to the length [C] of the non-depressed portion in the length direction is greater than 1.0.
[0073] Figure 1 This is a perspective view schematically showing an example of the mat material of the present invention.
[0074] like Figure 1 As shown, the mat material 10 has a substantially rectangular flat plate shape in a plan view, and the mat material 10 has: Figure 1 The first main surface 11 and the second main surface 12 are opposite to each other in the direction indicated by the double arrow T in the middle; in the length direction ( Figure 1 The first end face 13 and the second end face 14 facing each other in the direction indicated by the double arrow A in the middle; and the width direction ( Figure 1 The first side surface 15 and the second side surface 16 are opposite to each other in the direction indicated by the double arrow B in FIG.
[0075] The length of the mat material 10 is Figure 1 The length indicated by the double arrow A.
[0076] The width of the mat material 10 is Figure 1 The length indicated by the double arrow B.
[0077] The thickness of the mat material 10 is Figure 1 The length indicated by the double arrow T.
[0078] The first end surface 13 includes a convex portion 13 a that protrudes toward the second end surface 14 during winding, and non-protruding portions 13 b and 13 c that are disposed on both sides of the convex portion 13 a in the width direction and do not protrude toward the second end surface 14 .
[0079] The second end face 14 is provided with: a recessed portion 14a corresponding to the shape of the protruding portion 13a of the first end face 13 when winding; and non-recessed portions 14b, 14c arranged on both sides of the recessed portion 14a in the width direction and corresponding to the shapes of the non-protruding portions 13b, 13c of the first end face 13, respectively.
[0080] The length of the convex portion 13 a in the longitudinal direction (hereinafter also simply referred to as the length of the convex portion 13 a ) is the length indicated by the double-headed arrow C.
[0081] The shape of the convex portion 13a corresponds to the shape of the concave portion 14a. Therefore, the length of the concave portion 14a in the longitudinal direction (hereinafter also simply referred to as the length of the concave portion 14a) is the length indicated by the double-headed arrow C.
[0082] The length of the recessed portion 14 a in the width direction (hereinafter also simply referred to as the width of the recessed portion 14 a ) is the length indicated by the double-headed arrow E.
[0083] The shape of the recessed portion 14a corresponds to the shape of the convex portion 13a. Therefore, the length of the convex portion 13a in the width direction (hereinafter also simply referred to as the width of the convex portion 13a) is the length indicated by the double-headed arrow E.
[0084] Furthermore, the center of the convex portion 13a in the width direction coincides with the center of the concave portion 14a in the width direction.
[0085] The length of the non-recessed portions 14b and 14c in the longitudinal direction (hereinafter also referred to as the length of the non-recessed portions 14b and 14c) is the same as the length of the recessed portion 14a in the longitudinal direction, and is the length indicated by the double arrow C.
[0086] The length of the non-recessed portions 14 b and 14 c in the width direction (hereinafter also simply referred to as the width of the non-recessed portions 14 b and 14 c ) is the length indicated by the double arrow D.
[0087] The length of the non-protruding portions 13b and 13c in the width direction (hereinafter also referred to as the width of the non-protruding portions 13b and 13c) is the same as the length of the non-recessed portions 14b and 14c in the width direction, which is the length indicated by the double arrow D.
[0088] The portion of the mat 10 excluding the convex portion 13 a and the non-concave portions 14 b and 14 c is also referred to as a main body portion of the mat.
[0089] The length [A] of the mat material in the longitudinal direction corresponds to the length from the first end face to the second end face in each cross section when the mat material is cut along a plane parallel to the longitudinal direction and the thickness direction.
[0090] exist Figure 1 In the mat material 10 shown, when the length of the non-recessed portions 14b, 14c in the length direction is set to [D] and the length of the non-recessed portions 14b, 14c in the width direction is set to [C], the ratio [D / C] of the length [D] of the non-recessed portions 14b, 14c in the length direction to the length [C] of the non-recessed portions 14b, 14c in the width direction is greater than 1.0.
[0091] It should be noted that Figure 1 The ratio [D / C] in the mat material 10 shown is 2.1.
[0092] As described above, the length of the recessed portion 14 a in the longitudinal direction is the same as the length of the non-recessed portions 14 b and 14 c in the longitudinal direction.
[0093] The length of the concave portion 14a in the longitudinal direction is the same as the length of the convex portion 13a in the longitudinal direction. Furthermore, the length of the non-concave portions 14b and 14c in the width direction is the same as the length of the non-convex portions 13b and 13c in the width direction.
[0094] As described above, the feature of the mat material of the present invention that "the ratio [D / C] of the length [D] of the non-depressed portion in the width direction to the length [C] of the non-depressed portion in the length direction is greater than 1.0" can also be replaced by "the ratio [D / C] of the length [D] of the non-protruding portion in the width direction to the length [C] of the convex portion in the length direction is greater than 1.0".
[0095] In the mat of the present invention, the ratio [D / C] of the length [D] of the non-depressed portion in the width direction to the length [C] of the non-depressed portion in the longitudinal direction is preferably 1.2 or more, more preferably 1.6 or more.
[0096] In the mat material of the present invention, the center of the concave portion in the width direction [E C ] can be aligned with the center of the width direction of the mat [B C ] can be overlapped or not.
[0097] Figure 1 In the mat material 10 shown in the figure, the center of the width direction of the recessed portion 14a [E C ] and the center of the width direction of the mat material 10 [B C ]overlapping.
[0098] Therefore, the width of the non-recessed portion 14c is the same as that of the non-recessed portion 14b, and is the length indicated by the double arrow D. In addition, the width of the non-protruding portion 13c is the same as that of the non-protruding portion 13b, and is the length indicated by the double arrow D.
[0099] At the center of the width direction of the concave portion [E C ] is not aligned with the center of the mat material in the width direction [B C ] When the two non-depressed portions overlap, the widths of the two non-depressed portions are inconsistent. The width of one non-depressed portion is shorter than the width of the other non-depressed portion.
[0100] At this time, as [D] for calculating the ratio [D / C] of the length [D] of the non-recessed portion in the width direction to the length [C] of the non-recessed portion in the length direction, the length of the non-recessed portion with a shorter width is used.
[0101] Figure 2 It is a schematic diagram showing Figure 1 A perspective view showing an example of a process of winding a mat material around an exhaust gas treating body. Figure 3 is schematically shown in Figure 2 A perspective view of an example of a wound body prepared in the steps shown.
[0102] like Figure 2 As shown, by winding the mat material 10 to the exhaust gas treatment body 230, Figure 3 The wound body 250 is shown.
[0103] It should be noted that Figure 2 In the embodiment, the mat 10 is wound so that the first main surface 11 of the mat 10 is in contact with the exhaust gas treatment body 230 , but the mat 10 may be wound so that the second main surface 12 of the mat 10 is in contact with the exhaust gas treatment body 230 .
[0104] Figure 4 It shows that Figure 3 Schematic diagram of an example of a step of pressing a wound body into a casing.
[0105] Figure 4 In the figure, it is shown that Figure 3 The wound body 250 is shown pressed into the housing 220.
[0106] The direction in which the wound body 250 is pressed is from the upper side to the lower side of the paper.
[0107] Therefore, it can be said that of the two side surfaces (the first side surface 15 and the second side surface 16 ) of the mat 10 , the second side surface 16 is arranged on the downstream side in the pressing direction, and the first side surface 15 is arranged on the upstream side in the pressing direction.
[0108] When the wound body 250 is pressed into the casing 220 , a large shear force is applied to the mat 10 due to the friction between the mat 10 and the casing 220 and the friction between the mat 10 and the exhaust gas treating body 230 .
[0109] Specifically, a force is applied to pull the surface of the mat 10 constituting the wound body 250 toward the upstream side in the push-in direction.
[0110] The magnitude of deformation of the convex portion and the non-concave portion due to the shear force is determined by the arrangement order in the press-fitting direction and the connection area (distance) with the portion that becomes the mat body.
[0111] That is, the deformation increases as the distance to the upstream side in the pressing direction increases, and the deformation increases as the connection area (distance) to the portion that becomes the mat body decreases.
[0112] exist Figure 4 In the wound body 250 shown, the non-depressed portion 14 b of the mat 10 is the portion on the most upstream side in the press-fitting direction and is a portion that is easily deformed by the shear force.
[0113] However, in the mat material of the present invention, the ratio [D / C] of the length [D] of the non-recessed portion in the width direction to the length [C] of the non-recessed portion in the length direction is greater than 1.0, and therefore, the deformation of the non-recessed portion arranged on the upstream side of the pressing direction can be suppressed regardless of the orientation of the mat material.
[0114] In the mat material of the present invention, the configuration of the two side surfaces of the mat material in the pressing step is not particularly limited. Figure 4 As shown, the second side surface may be arranged on the downstream side in the pressing direction and the first side surface may be arranged on the upstream side in the pressing direction, or the first side surface may be arranged on the downstream side in the pressing direction and the second side surface may be arranged on the upstream side in the pressing direction.
[0115] However, when the center of the concave portion in the width direction does not overlap with the center of the mat material in the width direction, it is preferred that the side of the mat material with the non-concave portion having a short length in the width direction is arranged on the downstream side in the pressing direction, and the side of the mat material with the non-concave portion having a long length in the width direction is arranged on the upstream side in the pressing direction. By arranging the mat material in the above-mentioned orientation, the deformation of the non-concave portion arranged on the upstream side in the pressing direction can be further suppressed.
[0116] For example, assuming a case where the center of the recessed portion in the width direction does not overlap with the center of the mat in the width direction, the mat has two non-recessed portions having different lengths.
[0117] In this case, if the width of one non-depressed portion is set to D 1 , set the width of the other non-depressed part to D 2 , and set it to D 1 >D2 As long as the non-depressed portion with a shorter width, i.e., a width of D 2 The length of the non-depressed portion in the width direction [D 2 ] to the length of the non-depressed portion in the longitudinal direction [C] 2 / C] is 1.0 or more, it is included in the mat material of the present invention. This is because D 1 >D 2 , if [D 2 / C] is 1.0 or more, then of course [D 1 / C] is also greater than 1.0.
[0118] With a width of D 2 When the side surface of the mat material of the non-depressed portion is arranged on the upstream side in the pressing direction, since [D 2 / C] is 1.0 or more, so that deformation of the non-depressed portion can be suppressed.
[0119] With a width of D 1 When the side surface of the mat material of the non-depressed portion is arranged on the upstream side in the pressing direction, [D 1 / C] is 1.0 or more and greater than [D 2 / C], so it is the same as having a width of D 2 Compared with the case where the side surface of the mat material of the non-recessed portion is arranged on the upstream side in the press-fitting direction, deformation of the non-recessed portion is further suppressed.
[0120] In the mat of the present invention, the ratio [A / C] of the length [A] of the mat in the longitudinal direction to the length [C] of the non-depressed portion in the longitudinal direction is not particularly limited, but is preferably 10 or more.
[0121] When the ratio [A / C] of the length [A] of the mat in the longitudinal direction to the length [C] of the non-recessed portion in the longitudinal direction is 10 or more, the shape of the non-recessed portion becomes less likely to deform during press-fitting.
[0122] It should be noted that Figure 1 The ratio [A / C] in the mat 10 shown is 10.1.
[0123] As described above, the length [C] of the non-depressed portion in the longitudinal direction is the same as the length [C] of the recessed portion and the length [C] of the convex portion in the longitudinal direction.
[0124] Therefore, the feature of the mat material of the present invention that "the ratio [A / C] of the length [A] of the mat material in the length direction to the length [C] of the non-depressed portion in the length direction is greater than 10" can also be replaced by "the ratio [A / C] of the length [A] of the mat material in the length direction to the length [C] of the convex portion in the length direction is greater than 10" or "the ratio [A / C] of the length [A] of the mat material in the length direction to the length [C] of the concave portion in the length direction is greater than 10".
[0125] It should be noted that in Figure 1 to Figure 4 In the pad 10 shown, a convex portion 13a is formed on the first end face 13 and a concave portion 14a is formed on the second end face 14, but in the pad of the present invention, the number of convex portions formed on the first end face of the pad and the number of concave portions formed on the second end face can also be more than two.
[0126] In this case, focusing on the non-recessed portion arranged at a position closest to the first side surface of the mat material and the non-recessed portion arranged at a position closest to the second side surface, the ratio [D / C] of the length [D] of the non-recessed portion in the width direction to the length [C] of the non-recessed portion in the length direction is calculated.
[0127] The mat of the present invention is equivalent to the mat of the present invention if the ratio [D / C] of the non-depressed portions disposed closest to the first side surface of the mat and the ratio [D / C] of the non-depressed portions disposed closest to the second side surface of the mat are both 1.0 or more.
[0128] In the mat of the present invention, the thickness of the mat is not particularly limited, and is preferably 2 mm to 40 mm. If the thickness of the mat exceeds 40 mm, the mat loses its flexibility, and thus becomes difficult to handle when the mat is wound around the exhaust gas treatment body. In addition, the mat is prone to winding wrinkles and cracks.
[0129] If the thickness of the mat is less than 2 mm, the holding force of the mat is insufficient and the exhaust gas treatment body is easy to fall off. In addition, when the volume of the exhaust gas treatment body changes, it is difficult for the mat to absorb the volume change of the exhaust gas treatment body. Therefore, cracks are easy to occur in the exhaust gas treatment body.
[0130] The mat is composed of inorganic fibers.
[0131] The inorganic fibers are not particularly limited, but are preferably composed of at least one selected from the group consisting of alumina fibers, silica fibers, alumina silica fibers, mullite fibers, biosoluble fibers, and glass fibers.
[0132] When the inorganic fiber is at least one of alumina fiber, silica fiber, alumina silica fiber and mullite fiber, the heat resistance is excellent, so even when the exhaust gas treatment body is exposed to a sufficiently high temperature, it will not deteriorate, and the function as a mat material can be fully maintained. In addition, when the inorganic fiber is a biosoluble fiber, when the exhaust gas purification device is made using the mat material, even if the scattered inorganic fiber is inhaled, it will dissolve in the body, so it will not cause harm to the health of the operator.
[0133] The alumina fibers may contain additives such as calcium oxide, magnesium oxide, and zirconium oxide in addition to aluminum oxide.
[0134] As the composition ratio of alumina-silica fibers, Al2O3 is preferably 2 O 3 :SiO 2 =60:40 to 80:20, more preferably Al 2 O 3 :SiO 2 =70:30~74:26.
[0135] The mat can be produced by a needle punching method or a paper making method. A mat produced by a needle punching method is also referred to as a needle punched mat, and a mat produced by a paper making method is also referred to as a paper making mat.
[0136] In the case of the needle punching method, the average fiber length of the inorganic fibers is preferably 1 mm to 150 mm, more preferably 10 mm to 80 mm.
[0137] If the average fiber length of the inorganic fibers is less than 1 mm, the fiber length of the inorganic fibers is too short, so the interweaving of the inorganic fibers becomes insufficient, the winding property on the exhaust gas treatment body is reduced, and the mat is easily broken. In addition, if the average fiber length of the inorganic fibers exceeds 150 mm, the fiber length of the inorganic fibers is too long, so the number of fibers constituting the mat is reduced, and the density of the mat is reduced. As a result, the shear strength of the mat material is reduced.
[0138] In the case of the papermaking method, the average fiber length of the inorganic fibers is preferably 200 μm to 20,000 μm, more preferably 300 μm to 10,000 μm, and even more preferably 500 μm to 1,500 μm.
[0139] In the case of the needle punching method, interlaced points are formed on the surface or back side of the mat material.
[0140] The density of interlacing points is preferably 0.5 / cm 2 ≤ρ<18 pieces / cm 2 range.
[0141] When interlaced points are formed on both the front and back surfaces of the mat material, the interlaced point density ρ is the density of interlaced points measured on the main surface having a higher density of interlaced points, the front or back surface.
[0142] In the case of the needle punching method, it is preferred that at least one of the first area and the second area is arranged in a 25mm×25mm area on the surface or back of the mat material, the first area being a 4mm×4mm area with no interlacing points, and the second area being a 3mm×8mm area with no interlacing points.
[0143] By arranging at least one of the first region and the second region, a high surface pressure is exerted.
[0144] It should be noted that the main surface of the mat material on which the first region and / or the second region is arranged is determined to be the same main surface as the main surface on which the density of the interlaced points is measured.
[0145] Figure 5 This is a schematic diagram showing an example of the arrangement of interlaced points in the mat of the present invention.
[0146] Figure 5 The dimensions of the mat material 10 shown in the top view are 25 mm×25 mm.
[0147] exist Figure 5 In the example, the plurality of interlacing points 115 are arranged unevenly. Therefore, it can be said that a 4 mm×4 mm area ( Figure 5 The area indicated by the solid square in the figure) is the first area 117, and the area of 3 mm×8 mm where there is no interlacing point 115 ( Figure 5 The area represented by the dotted rectangle in the figure is the second area 118.
[0148] It should be noted that Figure 5 Not all of the first region 117 and the second region 118 are shown in the figure.
[0149] Figure 6 This is a schematic diagram showing an example of a mat material in which interlacing points are evenly arranged.
[0150] Figure 6 The dimensions of the mat material 10 shown in the top view are 25 mm×25 mm.
[0151] Figure 6 In the embodiment, the interlacing points 115 are evenly arranged at intervals of 2.8 mm.
[0152] Figure 6The 4 mm×4 mm square and 3 mm×8 mm rectangle shown each include one or more interlacing points. The 4 mm×4 mm square that does not correspond to the first region and the 3 mm×8 mm rectangle that does not correspond to the second region are marked with "×".
[0153] Therefore, in Figure 6 In the mat material shown, both the first area and the second area cannot be configured.
[0154] The method of counting the number of the first area and the second area in the 25 mm×25 mm area is as follows.
[0155] (1) A 4 mm x 4 mm region (first region) where no interlacing point is formed is found. At this time, a plurality of first regions are selected so as not to overlap with each other.
[0156] (2) Find a 3 mm × 8 mm area (second area) where no interlacing points are formed. At this time, multiple second areas are selected in a manner that they do not overlap with each other. However, the second area can overlap with the first area. If the second area overlaps with the first area, the area without interlacing points becomes larger, thereby increasing the surface pressure of the mat material.
[0157] (3) A 25 mm×25 mm region is selected in which the number of mutually non-overlapping first regions and the number of mutually non-overlapping second regions are the largest.
[0158] The above operation was performed on 10 samples and the average value was taken.
[0159] It should be noted that the above operations can be performed using commercially available image processing software or the like.
[0160] In the area of 25 mm×25 mm, a plurality of first areas and / or second areas are preferably arranged.
[0161] If a plurality of first regions and / or second regions are arranged in an area of 25 mm×25 mm, the surface pressure of the mat can be increased.
[0162] Configuring multiple first areas and / or second areas refers to a situation where the total number of first areas and the number of second areas is greater than 2, including a situation where multiple first areas are configured, a situation where multiple second areas are configured, and a situation where multiple first areas and multiple second areas are configured.
[0163] It is preferable that a third region of 4 mm×4 mm having four or more interlaced points is arranged in a region of 25 mm×25 mm on the front or back surface of the mat.
[0164] When the third region is provided, the inorganic fibers are strongly entangled with each other in the region, and thus the shear strength of the mat can be increased.
[0165] It should be noted that the method of counting the number of the third regions within the 25 mm×25 mm region is the same as the method of counting the number of the first regions described above.
[0166] It is preferred that an inorganic binder (also referred to as an inorganic bonding agent) is added to the surface of the inorganic fiber.
[0167] When an inorganic binder is attached to the surface of the inorganic fibers, the frictional resistance between the inorganic fibers increases due to the inorganic binder attached to the surface of the inorganic fibers, so that the holding force can be improved.
[0168] Examples of the inorganic binder include alumina sol and silica sol.
[0169] It is preferred that an organic binder (also referred to as an organic bonding agent) is added to the surface of the inorganic fibers.
[0170] When an organic binder is added to the surface of the inorganic fibers, the adhesion between the inorganic fibers can be improved, and the inorganic fibers can be prevented from scattering during the handling of the mat.
[0171] Examples of the organic binder include acrylic resins, acrylate emulsions, rubber emulsions, water-soluble organic polymers such as carboxymethyl cellulose and polyvinyl alcohol, thermoplastic resins such as styrene resins, and thermosetting resins such as epoxy resins.
[0172] It is preferred that an inorganic binder and an organic binder are attached to the surface of the inorganic fiber.
[0173] When an inorganic binder is attached to the surface of the inorganic fibers, the frictional resistance between the inorganic fibers increases due to the inorganic binder attached to the surface of the inorganic fibers, so that the holding force can be improved.
[0174] Furthermore, when an organic binder is added to the surface of the inorganic fibers, the adhesion between the inorganic fibers can be improved, and the inorganic fibers can be prevented from scattering during the handling of the mat.
[0175] The weight ratio of the inorganic binder to the mat material (weight of the inorganic binder / weight of the mat material) is preferably more than 0 wt % and not more than 10 wt %.
[0176] When the weight ratio of the inorganic binder to the mat material is within the above range, the holding force can be sufficiently improved.
[0177] The weight ratio of the organic binder to the mat material (weight of the organic binder / weight of the mat material) is preferably more than 0 wt % and not more than 10 wt %.
[0178] When the weight ratio of the organic binder to the mat material is within the above range, both the fiber scattering prevention effect and the high holding force can be achieved.
[0179] The contents of the organic binder and the inorganic binder contained in the mat can be measured, for example, by the following method.
[0180] First, a certain weight of the mat material whose content is to be measured is collected as a sample. Next, an organic solvent (e.g., tetrahydrofuran) in which the organic binder contained in the sample is dissolved is selected, and the organic binder is dissolved and separated from the sample using a Soxhlet extractor. At this time, the inorganic binder contained in the dissolved organic binder is also separated from the sample, and the organic binder and the inorganic binder are recovered in the organic solvent.
[0181] Next, an organic solvent containing the organic binder and the inorganic binder is placed in a crucible, and the organic solvent is evaporated and removed by heating. The residue remaining in the crucible is regarded as the total weight of the organic binder and the inorganic binder relative to the mat material, and the content (weight %) relative to the weight of the mat material is calculated.
[0182] Furthermore, the crucible was heated at 600°C for 1 hour to burn off the organic binder. Since the inorganic binder remained in the crucible, it was regarded as the content (weight %) of the inorganic binder relative to the total of the organic binder and the inorganic binder, and the content was calculated. The remainder was the content (weight %) of the organic binder.
[0183] In the mat material, it is preferred that the inorganic binder and the organic binder are attached to the surface of the inorganic fibers in a dispersed state.
[0184] If the inorganic binder and the organic binder are respectively attached to the surface of the inorganic fiber in a dispersed state, the inorganic binder is dispersed in the film formed by the organic binder. The film in this state has excellent mechanical strength, so it can prevent the inorganic fibers from sliding against each other and improve the holding force.
[0185] In the mat material, it is preferred that the covering layer composed of a mixture of an inorganic binder and an organic binder covers at least a part of the surface of the inorganic fibers.
[0186] The coating layer composed of a mixture of an inorganic binder and an organic binder has higher mechanical strength than a coating layer composed of only an organic binder, so that the coating layer is less likely to peel off, and the friction resistance between the inorganic fibers can be increased.
[0187] The covering layer is preferably formed by continuous flake-like mixture (a mixture of an inorganic binder and an organic binder).
[0188] When the covering layer is formed of the scaly mixture, a large number of irregularities derived from the scaly mixture are formed on the surface of the covering layer, and the frictional resistance between the inorganic fibers can be further increased.
[0189] Figure 7 This is an example of an electron microscope image of the mat material of the present invention which is magnified.
[0190] like Figure 7 As shown, a coating layer 130 composed of a mixture of an inorganic binder and an organic binder covers a portion of the surface of the inorganic fiber 120. The coating layer 130 is formed by a continuous scaly mixture of the inorganic binder and the organic binder. A granular mixture 140 of the inorganic binder and the organic binder is attached to the surface of the inorganic fiber 120.
[0191] It should be noted that whether the coating layer or the particles are composed of a mixture of an inorganic binder and an organic binder can be confirmed by combining field observation with an electron microscope and elemental analysis.
[0192] Figure 8 This is another example of an electron microscope image of the mat material of the present invention which is magnified.
[0193] like Figure 8 As shown, a coating layer 130 composed of a mixture of an inorganic binder and an organic binder covers a portion of the surface of the inorganic fiber 120. The coating layer 130 is formed by a continuous scaly mixture of the inorganic binder and the organic binder. A granular mixture 140 of the inorganic binder and the organic binder is attached to the surface of the inorganic fiber 120.
[0194] The thickness of the coating layer may be the same or different.
[0195] The shape of the coating layer with non-constant thickness is also called multi-step shape.
[0196] When the shape of the covering layer is multi-step, it can be said that the covering layer has irregularities on the surface, and thus the frictional resistance between the inorganic fibers can be further increased.
[0197] Whether the coating layer has surface irregularities, that is, whether the coating layer has a multi-step shape, is determined by magnifying the surface of the inorganic fiber 3000 times using a scanning electron microscope to check whether the coating layer has surface irregularities.
[0198] Fig. 9 This is another example of an electron microscope image of the mat material of the present invention which is magnified.
[0199] like Fig. 9 As shown, the coating layer 130 composed of a mixture of an inorganic binder and an organic binder covers a portion of the surface of the inorganic fiber 120. The coating layer 130 has a different thickness and is multi-stepped.
[0200] A granular mixture 140 of an inorganic binder and an organic binder is attached to the surface of the inorganic fibers 120 .
[0201] It is preferred that particles composed of a mixture of an inorganic binder and an organic binder adhere to the surface of the covering layer.
[0202] When particles composed of a mixture of an inorganic binder and an organic binder are attached to the surface of the covering layer, the frictional resistance between the inorganic fibers can be further increased compared to a case where the particles are not attached.
[0203] Fig.10 This is another example of an electron microscope image of the mat material of the present invention which is magnified.
[0204] like Fig.10 As shown, a coating layer 130 composed of a mixture of an inorganic binder and an organic binder covers a portion of the surface of the inorganic fiber 120. The coating layer 130 is formed by a continuous scaly mixture of the inorganic binder and the organic binder. The thickness of the coating layer 130 is different and is multi-stepped. A granular mixture 140 of the inorganic binder and the organic binder is attached to the surface of the coating layer 130.
[0205] The mat material preferably further contains a polymer dispersant.
[0206] When the mat material further contains a polymer-based dispersant, the organic binder and the inorganic binder can be easily attached to the surface of the inorganic fiber in a dispersed state.
[0207] The content of the polymer dispersant is preferably 50 ppm to 1000 ppm based on the weight of the inorganic fibers.
[0208] The mat material preferably has aggregates composed of an inorganic binder and an organic binder attached to the surface of the inorganic fibers.
[0209] The aggregate composed of the inorganic binder and the organic binder can form irregularities on the surface of the inorganic fibers, thereby increasing the friction between the inorganic fibers and improving the holding force.
[0210] The mat material may further contain a coagulant.
[0211] If the mat further contains a coagulant, the organic binder and the inorganic binder can be easily attached to the surface of the inorganic fibers in a coagulated state.
[0212] Whether the inorganic binder and the organic binder attached to the surface of the inorganic fiber are dispersed or aggregated can be confirmed by observing the surface of the inorganic fiber using SEM-EDX or the like.
[0213] The shear coefficient of the mat of the present invention is preferably 0.20 or more.
[0214] When the shear coefficient is 0.20 or more, when the exhaust gas treating body is pressed into a casing using the mat of the present invention, shearing of the mat is unlikely to occur.
[0215] The shear coefficient is obtained by dividing the shear failure load by the relaxation surface pressure.
[0216] The shear failure load can be obtained by Fig.11 The shear failure load is measured using the test apparatus shown.
[0217] Fig.11 1 is a conceptual diagram schematically showing a shear failure load test device.
[0218] Fig.11 The shear failure load test device 170 shown has test pieces 1a and 1b arranged on both sides of a stainless steel plate 173, and the outer sides thereof are clamped by a left clamp 171 and a right clamp 172. A plurality of protrusion members 174 are provided on the surfaces of the left clamp 171, the right clamp 172 and the stainless steel plate 173 on the surfaces in contact with the test pieces.
[0219] The test pieces 1 a and 1 b are fixed to the left jig 171 , the right jig 172 , and the stainless steel plate 173 by being pierced by the protruding member 174 .
[0220] In this state, the test piece was compressed until its bulk density (GBD) reached 0.3 g / cm 3 .
[0221] Next, if the stainless steel plate 173 is moved toward Fig.11 , the stainless steel plate 173 cannot be separated from the test pieces 1a and 1b and fall off because the stainless steel plate 173 is fixed to the test pieces 1a and 1b by the protrusion member 174. Therefore, when a shear force exceeding the shear failure load of the test pieces is applied to the test pieces 1a and 1b, the test pieces 1a and 1b are sheared and broken.
[0222] The shear force applied to the stainless steel plate when the test piece fails in shear was determined.
[0223] The shear failure load (kPa) can be obtained by dividing the obtained shear force by the area of the test piece. It should be noted that the shear failure load can also be measured using a test piece cut out of a part of the mat.
[0224] The relaxed surface pressure can be measured by the following procedure.
[0225] First, at room temperature, the mat was compressed to a bulk density of 0.3 g / cm 3 , measure the load after holding for 20 minutes.
[0226] The obtained load is divided by the area of the test piece to obtain the relaxed surface pressure (kPa). The relaxed surface pressure may be measured using a test piece obtained by cutting out a portion of the mat.
[0227] The back pressure of the mat material after firing is preferably 50 kPa or more.
[0228] The fired back surface pressure of the mat material can be measured by the following method using a hot surface pressure measuring device equipped with a heater at a plate portion that compresses the mat material as a test piece.
[0229] First, the test piece (mat) was compressed at room temperature to a bulk density of 0.3 g / cm 3 Then, the test piece was heated at a rate of 45°C to 900°C on one side and 650°C on the other side under compression, and the compression was released until the bulk density reached 0.27 g / cm 3 Then, the plate that compresses the mat material is moved at a speed of 1 inch (25.4 mm) / min to a bulk density of 0.3 / cm 3 . Until the bulk density reaches 0.27g / cm 3 The compression is released until the bulk density reaches 0.3 g / cm 3 After the compression was repeated 1000 times, the bulk density was measured to be 0.27 g / cm 3 The load obtained was divided by the area of the test piece to determine the surface pressure (kPa), which was taken as the surface pressure after firing.
[0230] [Making method of mat material]
[0231] The mat material of the present invention can be obtained, for example, by performing a cutting step of cutting a mat including inorganic fibers into a predetermined shape, or a molding step of molding the mat into a predetermined shape.
[0232] The mat can be obtained by, for example, a needle punching method and a papermaking method.
[0233] In the case of the needle punching method, for example, a mat can be obtained by the following steps: a spinning step of spinning a spinning mixture containing at least an inorganic compound and an organic polymer to produce an inorganic fiber precursor; a compression step of compressing the above-mentioned inorganic fiber precursor to produce a sheet-like object; a needle punching step of needle-punching at least one surface of the above-mentioned sheet-like object to produce a needle-punched body; and a firing step of firing the above-mentioned needle-punched body.
[0234] Hereinafter, specific examples of the spinning step, the compression step, the needling step, and the firing step will be described.
[0235] [Spinning process]
[0236] In the spinning step, a spinning mixture containing at least an inorganic compound and an organic polymer is spun to produce an inorganic fiber precursor.
[0237] In the spinning step, for example, a spinning mixture containing basic aluminum chloride aqueous solution and silica sol as raw materials is spun by a blowing method to produce an inorganic fiber precursor having an average fiber diameter of 3 μm to 10 μm.
[0238] [Compression process]
[0239] In the compression step, the inorganic fiber precursor obtained in the spinning step is compressed to produce a continuous sheet of a predetermined size.
[0240] [Acupuncture process]
[0241] In the needling step, at least one surface of the sheet-like object obtained in the compression step is subjected to needling treatment to produce a needling-treated body.
[0242] In the needling step, the needle arrangement density is preferably set to 0.5 needles / cm 2 More than and less than 18 / cm 2 .
[0243] The positions where the needles are arranged in the needling process correspond to the interlacing points in the mat. Therefore, by setting the needle arrangement density to 0.5 needles / cm 2 More than and less than 18 / cm 2 , the density of interlacing points can be obtained by a single needle punching process at 0.5 / cm 2 ≤ρ<18 pieces / cm 2 Range of pads.
[0244] However, when the same sheet-like object is subjected to a plurality of needling treatments, the arrangement density of the needles is not limited to the above range.
[0245] In addition, the arrangement of the needles was intentionally made uneven during the needling process, so that the arrangement of the intertwining points formed on the needle-punched body was made sparse and dense, and the density of the intertwining points was set to 0.5 pieces / cm 2 ≤ρ<18 pieces / cm 2 range, and within the 25 mm×25 mm area, a 4 mm×4 mm area (first area) without an interlacing point and / or a 3 mm×8 mm area (second area) without an interlacing point can be formed.
[0246] As a method for intentionally making the arrangement of the interlacing points uneven, for example, the following method can be cited: after the interlacing points are evenly arranged, a part of the interlacing points are additionally subjected to acupuncture treatment. In addition, a method of performing acupuncture treatment multiple times while moving the inorganic fiber precursor, a method of performing acupuncture treatment using a needle plate with needles arranged at unequal intervals, etc. can also be cited.
[0247] In the needling step, the needle may or may not penetrate the sheet-like object in the thickness direction.
[0248] [Firing process]
[0249] In the firing step, the needle-punched body is fired to obtain a mat composed of inorganic fibers.
[0250] The temperature for firing the needle-punched body is not particularly limited, but is preferably 1000°C to 1600°C.
[0251] Through the above steps, a pad can be obtained.
[0252] [Cutting process]
[0253] The mat obtained through the above steps can be cut into a predetermined shape to obtain the mat material of the present invention.
[0254] When producing the mat of the present invention, an adding step of adding an inorganic binder and / or an organic binder to the surface of the inorganic fibers constituting the mat or the mat may be performed.
[0255] [Attachment process]
[0256] In the attaching step, an inorganic binder and / or an organic binder is attached to the mat.
[0257] When no distinction is made between inorganic binders and organic binders, they are simply referred to as binders.
[0258] Examples of the inorganic binder include alumina sol and silica sol.
[0259] Examples of the organic binder include acrylic resins, acrylate emulsions, rubber emulsions, water-soluble organic polymers such as carboxymethyl cellulose and polyvinyl alcohol, thermoplastic resins such as styrene resins, and thermosetting resins such as epoxy resins.
[0260] As a method of applying the adhesive to the mat, for example, there is a method of bringing an adhesive mixed liquid in which a solvent and an adhesive are mixed into contact with the mat and then drying the mixed liquid.
[0261] Examples of a method for bringing the adhesive mixed liquid into contact with the mat include a method of immersing the mat in the adhesive mixed liquid and a method of dropping the adhesive mixed liquid onto the mat by a curtain coating method or the like.
[0262] The content of the inorganic binder in the binder mixture is preferably 0.05 wt % or more and 5 wt % or less.
[0263] The content of the organic binder in the binder mixture is preferably 0.05 wt % or more and 5 wt % or less.
[0264] That is, the binder mixture may contain only an inorganic binder as a binder, may contain only an organic binder, or may contain both an inorganic binder and an organic binder.
[0265] The binder mixed liquid may contain a polymer dispersant.
[0266] If the binder mixed liquid contains a polymer dispersant, the binder is dispersed in the binder mixed liquid. By bringing the binder mixed liquid in this state into contact with the mat, the binder can be attached to the surface of the inorganic fibers in a dispersed state.
[0267] Examples of the polymer dispersant include hydrophilic synthetic polymer substances such as anionic polymer dispersants such as polycarboxylic acids and / or their salts, naphthalenesulfonate formaldehyde condensates and / or their salts, polyacrylic acid and / or their salts, polymethacrylic acid and / or their salts, polyvinylsulfonic acid and / or their salts, and nonionic polymer dispersants such as polyvinyl alcohol, polyvinyl pyrrolidone, and polyethylene glycol; natural hydrophilic polymer substances such as gelatin, casein, and water-soluble starch; and hydrophilic semi-synthetic polymer substances such as carboxymethyl cellulose.
[0268] Among them, hydrophilic synthetic polymer substances are preferred, and anionic polymer dispersants are more preferred.
[0269] In addition, these polymeric dispersants may be used alone or in combination of two or more. In addition, a polymeric dispersant having a structure showing properties as an anionic polymeric dispersant and a structure showing properties as a nonionic polymeric dispersant may also be used.
[0270] The binder mixture may contain a coagulant.
[0271] If the binder mixed liquid contains a coagulant, the binder is in a coagulated state in the binder mixed liquid. By bringing the binder mixed liquid in this state into contact with the mat, the binder can be attached to the surface of the inorganic fibers in a coagulated state.
[0272] The binder mixed liquid may contain a polymer dispersant.
[0273] If the binder mixture contains a polymer dispersant, the binder is dispersed in the binder mixture. That is, the binder mixture becomes a dispersion in which the binder is dispersed in a dispersion medium. By bringing the binder mixture (dispersion) in this state into contact with the mat, the binder can be attached to the surface of the inorganic fiber in a dispersed state.
[0274] The binder mixture may contain a coagulant.
[0275] If the binder mixed solution contains a coagulant, the binder is in a coagulated state in the mixed solution. That is, the binder mixed solution becomes a coagulated dispersion in which a coagulate formed by the coagulation of the binder is dispersed in a dispersion medium. By bringing the mixed solution (coagulated dispersion) in this state into contact with the mat, the binder can be attached to the surface of the inorganic fiber in a coagulated state.
[0276] In the attaching step, the attachment of the inorganic binder and the attachment of the organic binder may be performed separately.
[0277] As a method for separately attaching an inorganic binder and an organic binder, for example, the following method can be cited: after an inorganic binder mixed solution containing an inorganic binder is brought into contact with the pad to attach the inorganic binder, the pad is further brought into contact with an organic binder mixed solution containing an organic binder to attach the organic binder. The order of attaching the inorganic binder and the organic binder is not particularly limited, and the inorganic binder may be attached first, or the organic binder may be attached first.
[0278] Through the above steps, the mat material of the present invention in which the inorganic binder and / or the organic binder is attached to the surface of the inorganic fiber can be obtained.
[0279] Next, the case where the papermaking method is used will be described.
[0280] In the case of the papermaking method, for example, a mat can be obtained through the following steps: a fiber opening step of fiberizing the inorganic fibers; a slurry preparation step of mixing the fiberized inorganic fibers with a solvent, an inorganic binder and an organic binder to prepare a slurry; a papermaking step of papermaking the slurry to obtain an inorganic fiber aggregate; and a drying step of drying the inorganic fiber aggregate.
[0281] Specific examples of the fiber opening step, the slurry preparation step, the papermaking step, and the drying step will be described below.
[0282] [Fiber opening process]
[0283] In the fiber opening step, inorganic fibers are shortened (also referred to as fiber opening) by a pulverizer such as a screen crusher or a mixer such as a pulper, and the fibers are adjusted to a desired fiber length.
[0284] The short-fibered inorganic fibers may be subjected to classification treatment as necessary, and preferably, a classification treatment is performed to remove part or all of the inorganic fibers having a fiber length of 200 μm or less.
[0285] Examples of the classification treatment include classification treatment using a dry centrifugal classifier (also referred to as a dry cyclone separator), a wet centrifugal classifier (also referred to as a wet cyclone separator), and the like.
[0286] [Slurry preparation process]
[0287] In the slurry preparation process, the fiberized inorganic fibers are mixed with a solvent, an inorganic binder, and an organic binder to prepare a slurry.
[0288] The order of mixing the inorganic binder and the organic binder is not particularly limited. It is preferred to first mix the inorganic fiber and the inorganic binder, and then add the organic binder after standing for a period of time. By initially mixing the inorganic fiber and the inorganic binder, the inorganic binder is surely attached to the surface of the inorganic fiber, thereby increasing the friction between the inorganic fibers and increasing the surface pressure. Furthermore, an agglomerate formed by agglomerating the organic binder and the inorganic binder using a coagulant may also be added to the slurry.
[0289] [Copying process (molding process)]
[0290] In the papermaking process, after the slurry is flowed into a former having a filtering mesh formed on the bottom surface, the solvent in the slurry is desolvated to obtain an inorganic fiber aggregate.
[0291] The shape of the former at this time becomes the shape of the mat. That is, it can be said that the papermaking process also serves as the forming process. Therefore, it is preferred to set the shape of the former in advance to the shape of the mat material to be obtained.
[0292] The desolvation treatment is not particularly limited as long as the solvent contained in the pad can be removed. For example, the solvent can be removed by compression, rotation, suction, decompression, or the like.
[0293] [Drying process]
[0294] In the drying step, the inorganic fiber aggregate is dried while being compressed by a method such as compression drying using a hot plate of a pressurized dryer or the like.
[0295] Through the above steps, the mat material of the present invention can be obtained in which the inorganic binder and / or the organic binder is attached to the surface of the inorganic fibers.
[0296] [Exhaust gas purification device]
[0297] The exhaust gas purification device of the present invention comprises: an exhaust gas treatment body; a housing that accommodates the exhaust gas treatment body; and a mat that is arranged between the exhaust gas treatment body and the housing to hold the exhaust gas treatment body. The exhaust gas purification device is characterized in that the mat is the mat of the present invention.
[0298] In the exhaust gas purifying device of the present invention, since the mat material of the present invention is disposed between the exhaust gas treating body and the casing, the exhaust gas treating body can be stably held.
[0299] Fig.12 This is a cross-sectional view schematically showing an example of the exhaust gas purification device of the present invention.
[0300] like Fig.12 As shown, the exhaust gas purification device 200 includes: a housing 220; an exhaust gas treatment body 230 accommodated in the housing 220; and a mat 10 disposed between the exhaust gas treatment body 230 and the housing 220. The mat 10 is the mat of the present invention.
[0301] The exhaust gas treatment body 230 is a columnar exhaust gas treatment body having a plurality of channels 231 arranged side by side in the length direction through the channel wall 232. It should be noted that, at the end of the housing 220, an inlet pipe for introducing the exhaust gas discharged from the internal combustion engine and an exhaust pipe for discharging the exhaust gas passing through the exhaust gas purification device to the outside are connected as needed.
[0302] It should be noted that in Fig.12 In the exhaust gas purification device 200 shown, an exhaust gas filter (honeycomb filter) in which any one of the channels is sealed with a sealing material 233 is used as the exhaust gas treatment body 230, but a catalyst carrier in which any end surface is not sealed with a sealing material may also be used.
[0303] like Fig.12 As shown, the exhaust gas ( Fig.12 , G represents exhaust gas, and arrows represent the flow of exhaust gas) flows into a channel 231 opened at the exhaust gas inlet side end face 230a of the exhaust gas treatment body (honeycomb filter) 230, and passes through the channel wall 232 separating the channel 231. At this time, PM in the exhaust gas is captured by the channel wall 232, and the exhaust gas is purified. The purified exhaust gas flows out from the other channels 231 opened at the exhaust gas outlet side end face 230b and is discharged to the outside.
[0304] It should be noted that the exhaust gas inlet side end surface 230a and the exhaust gas outlet side end surface 230b determined by the direction of the exhaust gas flowing into the exhaust gas purification device have nothing to do with the direction of the pressurization.
[0305] [Method for manufacturing exhaust gas purification device]
[0306] The manufacturing method of the exhaust gas purification device of the present invention is characterized by comprising a pressing step: after the mat of the present invention is wound around the exhaust gas treatment body, it is pressed into the housing by a hard filling method, a pre-calibration method or a post-calibration method.
[0307] The hard filling method, the pre-calibration method, and the post-calibration method all require a step of pressing the exhaust gas treatment body with the mat wound around it into the housing. Therefore, the mat of the present invention can suppress the displacement and deformation of the mat during pressing, and is therefore particularly suitable for the above methods.
[0308] The hard packing method is a method of preparing a cylindrical shell having a predetermined inner diameter in advance and press-fitting the exhaust gas treating body with the mat material wound around it into the shell.
[0309] The pre-calibration method is a method of reducing the diameter of a cylindrical casing having a predetermined inner diameter once and then pressing the exhaust gas treating body wound with a mat material into the casing.
[0310] The post-calibration method is a method of pressing an exhaust gas treating body wrapped with a mat into a cylindrical housing having a predetermined inner diameter, and then reducing the diameter of the housing together with the exhaust gas treating body and the mat.
[0311] The above methods all apply a large shear force to the mat material when pressing it in, which easily causes the mat material to deflect and deform.
[0312] On the other hand, the mat of the present invention can suppress the deviation and deformation of the mat during press-fitting, and is therefore particularly suitable for a method of manufacturing an exhaust gas purifying device including such a press-fitting step.
[0313] In the method for manufacturing an exhaust gas purifying device of the present invention, preferably, in the press-fitting step, the mat is press-fitted into the casing with the first side surface disposed on the upstream side and the second side surface disposed on the downstream side.
[0314] In particular, when the width direction length of the non-recessed portion arranged on the first side is longer than the width direction length of the non-recessed portion arranged on the second side, it is preferred to arrange the first side of the mat material on the upstream side and the second side on the downstream side and press it into the shell.
[0315] The following matters are disclosed in this specification.
[0316] The present disclosure (1) is a mat material which is a substantially rectangular mat material in plan view and contains inorganic fibers, and is characterized in that:
[0317] The mat material comprises: a first main surface and a second main surface facing each other in the thickness direction; a first end surface and a second end surface facing each other in the length direction which becomes the winding direction; and a first side surface and a second side surface facing each other in the width direction which is orthogonal to the thickness direction and the length direction.
[0318] The first end surface is formed with: a convex portion that protrudes toward the second end surface when winding; and a non-protruding portion that is arranged on both sides of the convex portion in the width direction and does not protrude toward the second end surface,
[0319] The second end surface is formed with: a concave portion corresponding to the shape of the convex portion of the first end surface during winding; and a non-concave portion arranged on both sides of the concave portion in the width direction and corresponding to the shape of the non-convex portion of the first end surface,
[0320] A ratio [D / C] of a length [D] of the non-recessed portion in the width direction to a length [C] of the non-recessed portion in the length direction is 1.0 or more.
[0321] The present disclosure (2) is the mat material described in the present disclosure (1), which is a needle punched mat.
[0322] The present disclosure (3) is the mat material described in the present disclosure (2), which is a mat material having a plurality of interlacing points formed by needle punching on at least one of the surface or the back surface, wherein at least one of the first area and the second area is arranged in an area of 25mm×25mm, the first area is a 4mm×4mm area where the above-mentioned interlacing points do not exist, and the second area is a 3mm×8mm area where the above-mentioned interlacing points do not exist.
[0323] The present disclosure (4) is the mat material according to the present disclosure (2) or (3), wherein the average fiber length of the inorganic fibers is 1 mm to 150 mm.
[0324] The present disclosure (5) is the mat material described in the present disclosure (1), which is a paper-made mat.
[0325] The present disclosure (6) is the mat material according to the present disclosure (5), wherein the average fiber length of the inorganic fibers is 200 μm to 20,000 μm.
[0326] The present disclosure (7) is a mat material in combination with any one of the present disclosures (1) to (6), wherein an inorganic binder is attached to the surface of the inorganic fiber.
[0327] The present disclosure (8) is a mat material in combination with any one of the present disclosures (1) to (6), wherein an organic binder is attached to the surface of the inorganic fibers.
[0328] The present disclosure (9) is a mat material in combination with any one of the present disclosures (1) to (6), wherein an inorganic binder and an organic binder are attached to the surface of the inorganic fibers.
[0329] The present disclosure (10) is a mat material in combination with any one of the present disclosures (1) to (9), further comprising a polymer-based dispersant.
[0330] The present disclosure (11) is the mat material described in the present disclosure (9), wherein the inorganic binder and the organic binder are attached to the surface of the inorganic fiber in a dispersed state.
[0331] The present disclosure (12) is the mat material described in the present disclosure (9), wherein an aggregate composed of the inorganic binder and the organic binder is attached to the surface of the inorganic fiber.
[0332] The present disclosure (13) is the mat material according to the present disclosure (12), wherein a coating layer composed of a mixture of the inorganic binder and the organic binder covers at least a portion of the surface of the inorganic fiber.
[0333] The present disclosure (14) is the mat material according to the present disclosure (13), wherein the covering layer is formed by a continuous scaly mixture of the inorganic binder and the organic binder.
[0334] The present disclosure (15) is the mat material described in the present disclosure (13) or (14), wherein the coating layer has a multi-step shape.
[0335] The present disclosure (16) is a mat material in combination with any one of the present disclosures (13) to (15), wherein a granular mixture of the inorganic binder and the organic binder is attached to the surface of the covering layer.
[0336] The present disclosure (17) is a mat material in any combination with any one of the present disclosures (1) to (16), wherein the ratio [A / C] of the length [A] of the mat material in the above-mentioned length direction to the length [C] of the above-mentioned non-depressed portion in the above-mentioned length direction is greater than 10.
[0337] The present disclosure (18) is an exhaust gas purification device, which comprises: a housing; an exhaust gas treatment body; and a mat material arranged between the housing and the exhaust gas treatment body.
[0338] The exhaust gas purification device is characterized in that the mat material is a mat material in any combination with any one of (1) to (17) of the present disclosure.
[0339] The present disclosure (19) is a method for manufacturing an exhaust gas purification device, characterized in that it has a pressing step: after a mat material of any combination of any one of the present disclosures (1) to (17) is wound around an exhaust gas treatment body, it is pressed into a shell by a hard filling method, a pre-calibration method or a post-calibration method.
[0340] (Example)
[0341] Examples that more specifically disclose the present invention are shown below. In the following examples, mats were produced by a needle punching method, but the present invention is not limited to these examples.
[0342] (Example 1)
[0343] (a) Spinning process
[0344] In the alkaline aluminum chloride aqueous solution prepared so that the Al content is 70 g / l and Al:Cl=1:1.8 (atomic ratio), the composition ratio of the inorganic fiber after firing is Al:Cl=1:1.8. 2 O 3 :SiO 2 =72:28 (weight ratio), and further an appropriate amount of an organic polymer (polyvinyl alcohol) was added to prepare a mixed solution.
[0345] The obtained mixed solution was concentrated to prepare a spinning mixture, and the spinning mixture was spun by a blowing method to prepare an inorganic fiber precursor having an average fiber diameter of 5.1 μm.
[0346] (b) Compression process
[0347] The inorganic fiber precursor obtained in the spinning step (a) is compressed to produce a continuous sheet.
[0348] (c) Acupuncture process
[0349] The sheet-like material obtained in the compression step (b) is subjected to a needle punching treatment a plurality of times using a needle plate on which needles are provided at a predetermined density to produce a needle-punched body.
[0350] First, a needle plate with needles mounted at a predetermined density is prepared. Next, the needle plate is disposed above one surface of a sheet-like object, and a needle-punched body is produced by moving the needle plate up and down once in the thickness direction of the sheet-like object multiple times while moving the inorganic fiber precursor. At this time, the needles are penetrated until the barbs formed at the tip of the needles completely penetrate the surface on the opposite side of the sheet-like object.
[0351] (d) Firing process
[0352] The needle-punched body obtained in the above-mentioned needling step (c) was continuously fired at a maximum temperature of 1250°C to produce a fired sheet composed of inorganic fibers containing alumina and silica in a ratio of 72 parts by weight: 28 parts by weight. The average fiber diameter of the inorganic fibers was 5.1 μm, and the minimum fiber diameter was 3.2 μm. The bulk density of the fired sheet obtained in this way was 0.15 g / cm 3 , basis weight is 1400g / m 2 The density of interlacing points is 9 / cm 2In the area of 25 mm×25 mm, there are arranged 10 areas of 4 mm×4 mm without interlacing points, namely the first area, and 4 areas of 3 mm×8 mm without interlacing points, namely the second area.
[0353] (e) Cutting process
[0354] The fired needle-punched body is cut to produce a mat.
[0355] The pad has a length [A] of 348.0 mm in the longitudinal direction and a length [B] of 93.5 mm in the width direction, and is roughly rectangular when viewed from above. The length [C] of the convex portion is 20.0 mm, and the width [D] of the non-concave portion is 20.0 mm. 1 and D 2 ] is 31 mm, the width of the convex part [E] is 31.5 mm, and the center of the concave part in the width direction [E C ] and the center of the pad width direction [B C ]overlapping.
[0356] (f) Attachment process
[0357] (f-1) Organic binder mixed solution preparation process
[0358] An acrylic emulsion as an organic binder was diluted with water to prepare an organic binder mixed liquid having a solid content concentration of 2.0 wt %.
[0359] (f-2) Inorganic binder mixed solution preparation process
[0360] Alumina as an inorganic binder was diluted with water, and a polymer dispersant was added and stirred sufficiently to prepare an inorganic binder mixed liquid having a solid content concentration of inorganic particles of 2.0 wt % and a concentration of the polymer dispersant of 1000 ppm.
[0361] (f-3) Binder Mixture Preparation Step
[0362] The organic binder mixture obtained in the above-mentioned (f-1) organic binder mixture preparation step is added to the inorganic binder mixture obtained in the above-mentioned (f-2) inorganic binder mixture preparation step in a manner to form a weight ratio of 1:1, and the mixture is fully stirred to prepare a binder mixture in which the organic binder has a solid content concentration of 1.0 wt%, the inorganic binder has a solid content concentration of 1.0 wt%, and the concentration of the above-mentioned polymer dispersant is 500 ppm.
[0363] (f-4) Contact process
[0364] The adhesive mixed solution obtained in the above-mentioned (f-3) adhesive mixed solution preparation step is brought into contact with the mat obtained in the (e) cutting step by curtain coating.
[0365] (f-5) Dehydration process
[0366] The mat to which the binder mixed solution was applied obtained in the contact step (f-4) was subjected to suction dehydration by a dehydrator, thereby preparing a state in which 100 parts by weight of the binder mixed solution was applied to 100 parts by weight of the inorganic fibers.
[0367] (f-6) Drying process
[0368] The mat after the dehydration step (f-5) was dried in a dryer to produce the mat material of Example 1.
[0369] (Examples 2 to 6 and Comparative Examples 1 to 3)
[0370] Except that the cut shape in the cutting step (e) was changed to satisfy the conditions in Table 1, the same procedure as in Example 1 was followed to produce mats of Examples 2 to 6 and Comparative Examples 1 to 3.
[0371] It should be noted that [D 1 ] represents the width of the non-depressed portion on the first side, [D 2 ] represents the width of the non-depressed portion on the second side surface.
[0372] (Press-in test)
[0373] The mat materials of Examples 1 to 3 and Comparative Examples 1 to 2 were wound onto an exhaust gas treatment body having a diameter of 103 mm and a length of 105 mm. The obtained wound body having a diameter of 115 mm was pressed into a stainless steel outer shell having an inner diameter of 110.8 mm at a speed of 500 mm / min using a pressing fixture having a taper angle of 4.5° and a drawing diameter of 110.7 mm, with the first side of the mat material being the upstream side and the second side being the downstream side.
[0374] When the mat is wound around the exhaust gas treatment body, the length [L 0 ], after being pressed in, the length [L 1 ], and the difference [ΔL] was taken as the deformation amount (offset amount) of the mat material, and evaluated according to the following criteria.
[0375] It should be noted that the mat materials of Examples 4 to 6 and Comparative Example 3 were wound onto an exhaust gas treatment body having a diameter of 129 mm and a length of 105 mm, and the obtained wound body having a diameter of 141 mm was pressed into a stainless steel outer shell having an inner diameter of 145.4 mm at a speed of 500 mm / min using a pressing fixture having a taper angle of 4.5° and a drawing diameter of 145.3 mm, with the first side of the mat material being the upstream side and the second side being the downstream side.
[0376] [Evaluation criteria]
[0377] ◎: The amount of deformation (deviation) is 6 mm or less, and the deformation of the mat material is particularly suppressed.
[0378] ○: The deformation amount (offset amount) exceeds 6 mm and is 8 mm or less, and the deformation of the mat material is fully suppressed.
[0379] ×: The amount of deformation (deviation) exceeded 8 mm, and the deformation of the mat material was not sufficiently suppressed.
[0380] [Table 1]
[0381]
[0382] As shown in Table 1, it is confirmed that the mat materials of the present invention can suppress deformation and displacement of the mat materials during pressing. Furthermore, from the comparison between Examples 1 to 5 and Example 6, it can be seen that by making the ratio [A / C] of the length [A] of the mat material in the longitudinal direction to the length [C] of the non-depressed portion in the longitudinal direction be 10 or more, the deformation and displacement of the mat material during pressing can be particularly suppressed.
[0383] Description of Reference Numerals
[0384] 1a, 1b test piece
[0385] 10 cushion material
[0386] 11 Main side 1
[0387] 12Second Main Side
[0388] 13 1st end face
[0389] 13a convex part
[0390] 13b, 13c non-protruding part
[0391] 14 2nd end face
[0392] 14a recess
[0393] 14b, 14c non-depressed portion
[0394] 15 Side 1
[0395] 16 Side 2
[0396] 115 Intertwining Points
[0397] 117 Area 1
[0398] 118 Area 2
[0399] 120 Inorganic fiber
[0400] 130 Coating
[0401] 140 Granular mixture
[0402] 170 Shear failure load test device
[0403] 171 Left side clamp
[0404] 172 Right side clamp
[0405] 173 Stainless steel plate
[0406] 174 protruding member
[0407] 200 Exhaust gas purification device
[0408] 220 Housing
[0409] 230 Exhaust gas treatment body
[0410] 230a Exhaust gas inflow side end face
[0411] 230b Exhaust gas outflow side end face
[0412] 231 Channel
[0413] 232 Channel wall
[0414] 233 Sealing material
[0415] 250 winding body
Claims
1. A mat material comprising inorganic fibers and having a substantially rectangular shape in plan view, characterized in that: The mat material comprises: a first main surface and a second main surface facing each other in the thickness direction; a first end surface and a second end surface facing each other in the length direction which becomes the winding direction; and a first side surface and a second side surface facing each other in the width direction which is orthogonal to the thickness direction and the length direction. The first end surface is formed with: a convex portion that protrudes toward the second end surface when winding, and a non-protruding portion that is arranged on both sides of the convex portion in the width direction and does not protrude toward the second end surface, The second end surface is formed with: a concave portion corresponding to the shape of the convex portion of the first end surface during winding, and a non-concave portion arranged on both sides of the concave portion in the width direction and corresponding to the shape of the non-convex portion of the first end surface, A ratio D / C of a length D of the non-recessed portion in the width direction to a length C of the non-recessed portion in the length direction is 1.0 or more. The mat material according to claim 1 , which is a needle punched mat.
3. The mat material according to claim 2, wherein: The mat material has a plurality of interlacing points formed by needle punching on at least one of the surface or the back surface, and at least one of the first area and the second area is arranged in an area of 25mm×25mm, the first area is a 4mm×4mm area where the interlacing points do not exist, and the second area is a 3mm×8mm area where the interlacing points do not exist.
4. The mat material according to claim 2 or 3, wherein: The average fiber length of the inorganic fibers is 1 mm to 150 mm. The mat material according to claim 1 , which is a paper-made mat.
6. The mat material according to claim 5, wherein: The average fiber length of the inorganic fibers is 200 μm to 20000 μm.
7. The mat material according to any one of claims 1 to 6, wherein The inorganic binder is attached to the surface of the inorganic fiber.
8. The mat material according to any one of claims 1 to 6, wherein The organic binder is attached to the surface of the inorganic fibers.
9. The mat material according to any one of claims 1 to 6, wherein Inorganic binders and organic binders are attached to the surfaces of the inorganic fibers. 10 . The mat material according to claim 1 , further comprising a polymer dispersant.
11. The mat material according to claim 9, wherein: The inorganic binder and the organic binder are attached to the surface of the inorganic fiber in a dispersed state.
12. The mat material according to claim 9, wherein: Aggregates composed of the inorganic binder and the organic binder are attached to the surfaces of the inorganic fibers.
13. The mat material according to claim 12, wherein: The coating layer composed of a mixture of the inorganic binder and the organic binder covers at least a portion of the surface of the inorganic fiber.
14. The mat material according to claim 13, wherein: The coating layer is formed by a continuous scaly mixture of the inorganic binder and the organic binder.
15. The mat material according to claim 13 or 14, wherein: The coating layer has a multi-step shape.
16. The mat material according to any one of claims 13 to 15, wherein A particle-shaped mixture of the inorganic binder and the organic binder adheres to the surface of the coating layer.
17. The mat material according to any one of claims 1 to 16, wherein A ratio A / C of a length A of the mat material in the longitudinal direction to a length C of the non-depressed portion in the longitudinal direction is 10 or more.
18. An exhaust gas purification device, comprising: a housing; an exhaust gas treatment body; and a mat material disposed between the housing and the exhaust gas treatment body, The exhaust gas purification device is characterized in that The mat material is the mat material according to any one of claims 1 to 17.
19. A method for manufacturing an exhaust gas purification device, characterized in that: A pressing step is provided: after the mat material according to any one of claims 1 to 17 is wound around the exhaust gas treatment body, the mat material is pressed into the housing by a hard filling method, a pre-calibration method or a post-calibration method.
Citation Information
Patent Citations
Sheet member and exhaust gas purifying device
JP2011241837A